the Existence and Function of the Japanese Bunker in Banyuwangi: Eksistensi dan Fungsi Bunker Jepang di Banyuwangi - Dhalia Soetopo; Andini Ramadhani3; Fatimatuzahro; Nafisa Desi Wulandari; Irsyad Arjuna Valentino Mesy6; Sri Suci Dewi Wulandari; miskawi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the existence of Japanese bunkers in Banyuwangi by examining their physical condition, location, function, and the perceptions of the local community toward these historical relics. The research employs a descriptive qualitative method with a historical approach. Data were collected through field observations, documentation, and interviews with members of the local community as well as related stakeholders. The results indicate that Japanese bunkers are distributed across several strategic locations in Banyuwangi, with physical conditions ranging from relatively well-preserved to significantly damaged. During the Japanese occupation, these bunkers functioned as defense structures, military surveillance posts, and storage facilities for weapons and military equipment. Currently, local community perceptions generally recognize the bunkers as historical relics of war. However, many community members have limited understanding of their original functions and historical significance. These findings highlight the importance of preserving and documenting such historical remains as part of local cultural heritage and as valuable resources for historical education. This study aims to describe the existence of Japanese bunkers in Banyuwangi by examining their physical condition, location, function, and the perceptions of the local community toward these historical relics. The research employs a descriptive qualitative method with a historical approach. Data were collected through field observations, documentation, and interviews with members of the local community as well as related stakeholders. The results indicate that Japanese bunkers are distributed across several strategic locations in Banyuwangi, with physical conditions ranging from relatively well-preserved to significantly damaged. During the Japanese occupation, these bunkers functioned as defense structures, military surveillance posts, and storage facilities for weapons and military equipment. Currently, local community perceptions generally recognize the bunkers as historical relics of war. However, many community members have limited understanding of their original functions and historical significance. These findings highlight the importance of preserving and documenting such historical remains as part of local cultural heritage and as valuable resources for historical education.